Knowledge access and satisfaction of pregnant women on the use of the National Health Insurance Scheme in accessing health care in the Bia East District of Ghana - Livingstone Asem; Geoffrey Adebayo Asalu; Shaibu Seidu; Blessing Yayra Amable; Gifty Emefa Kpordze; Wisdom Kwami Takramah; Emmanuel Amaglo; Senanu Kwesi Dzokoto (BMC, 2024)
Abstract Introduction In Ghana, access to health care is impeded mostly by financial capital. The National Health Insurance (NHIS) rolled out in 2003 was an attempt to remove cost as a barrier and help bridge this gap in health access. Despite the benefits, enrolment and use have been low. Hence a need to assess the knowledge, access and satisfaction of pregnant women on the use of NHIS to access healthcare. Materials and methods The study employed a facility-based descriptive cross-sectional study. A structured questionnaire was used to collect data from a total of 387 pregnant women using a simple random sampling technique. Data was collected to gain an insight into the knowledge, accessibility and satisfaction level of pregnant women on the usage of NHIS. Data was analyzed using Stata version 17.0 and results were presented in frequency tables. Results Overall, most of the pregnant women had a good knowledge of 228 (67.5%) and a high accessibility of 279 (82.5%) to using NHIS use it in accessing healthcare. Whilst for satisfaction, 311 (92.01%) said they were satisfied with the services and would prefer the use of NHIS to out-of-pocket payment. Conclusion In the current study the level of knowledge, accessibility, and satisfaction of NHIS is high. However, to sustain this gain, a multidimensional approach to community education should be intensified.